Some Technological Properties of Sawn Board Eucalyptus Camaldulensis Denh.Grown In Askikalak - Taha, Mohammed A. Y. (Science Journal of University of Zakho, 2015)
This study deals with wood density and static bending boards property of Eucalyptus camaldulensis Den. It was conducted using standardized, defect-free test specimens. Boards of air drying showed lowest value (749.117 kg/cm²) of static bending when compared with kiln (812.267kg/cm²) and solar (815.267kg/cm²) drying respectively, whereas, the quarter sawing boards recorded the lowest rates (586.633kg/cm²) when compared with flat sawn boards (1008.467kg/cm²), Also 2cm thickness level achieved the lowest rate (747.367kg/cm²) when compared with other two levels 4cm (812.650 kg/cm²) and 6cm (837.633kg/cm²) of thickness. But, there were no any significant effects of wood density on the studied factors. E. camaldulensis in Kurdistan Region of Iraq has potential for traditional uses and by itself it can be harvested by applying suitable techniques at plantation areas, in saw mills and drying for utilization.